2016
DOI: 10.3892/ol.2016.5484
|View full text |Cite
|
Sign up to set email alerts
|

Human antigen R as a predictive marker for response to gemcitabine-based chemotherapy in advanced cisplatin-resistant urothelial cancer

Abstract: Abstract. In patients with advanced urothelial cancer (UC), a combination of cisplatin (CDDP) and gemcitabine (GEM) is the most commonly used first-line systematic chemotherapy regimen. Although no standard regime for the treatment of CDDP-resistant UC has been established, GEM-based regimens are frequently used in these patients. In other types of cancer, human antigen R (HuR) status in cancer cells is closely associated with patient response to GEM. The aim of the present study was to establish the predictiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…We reported that human antigen-R (HuR) expression is a useful predictor of response to gemcitabine-based chemotherapy in patients with cisplatin-resistant UC (12). Class III β-tubulin (TUBB3) expression was also reported to predict the clinical benefits of paclitaxel-based second-line chemotherapy in these patients (13).…”
mentioning
confidence: 99%
“…We reported that human antigen-R (HuR) expression is a useful predictor of response to gemcitabine-based chemotherapy in patients with cisplatin-resistant UC (12). Class III β-tubulin (TUBB3) expression was also reported to predict the clinical benefits of paclitaxel-based second-line chemotherapy in these patients (13).…”
mentioning
confidence: 99%